2017
DOI: 10.1007/s11743-017-1974-4
|View full text |Cite
|
Sign up to set email alerts
|

Stearic Acid Modified Stearyl Alcohol Oleogel: Analysis of the Thermal, Mechanical and Drug Release Properties

Abstract: The present study delineates the effect of stearic acid on the properties of stearyl alcohol oleogel. Herein, a series of oleogels were prepared by mixing different proportions of fatty alcohol (Stearyl alcohol; gelator) and fatty acid (stearic acid; co‐gelator). The characterization of the oleogels was done by thermal, macro‐scale stress relaxation, drug release, and antimicrobial studies. The oleogels were formed by the self‐assembly of stearyl alcohol/stearic acid. Thermal studies indicated that the stearic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…Especially, the oleogel applied most often in food preservation is a three‐dimensional network structure formed by gel molecules under various forces, while the oil droplet molecules are inlaid in it. The oleogel can effectively change the rheological properties of oil, thereby improving its stability as well as exerting a controlled‐release effect on the active substance contained in the oleogel . EC is one of a variety of cellulose ether derivatives that are commonly used in the food and pharmaceutical industries because of their excellent film‐forming properties and their ability to act as an effective moisture barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the oleogel applied most often in food preservation is a three‐dimensional network structure formed by gel molecules under various forces, while the oil droplet molecules are inlaid in it. The oleogel can effectively change the rheological properties of oil, thereby improving its stability as well as exerting a controlled‐release effect on the active substance contained in the oleogel . EC is one of a variety of cellulose ether derivatives that are commonly used in the food and pharmaceutical industries because of their excellent film‐forming properties and their ability to act as an effective moisture barrier.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of both emulsifiers at lower content may reduce the reorganizational capability of gelator molecules. This significant decrease also means a high elastic component, as confirmed through F R values and low viscous components of the oleogels [ 45 ]. It is quite evident that even a lower amount of emulsifier affects the mechanical properties of the formulation [ 41 ].…”
Section: Resultsmentioning
confidence: 94%
“…However, among TWEEN-80, all the formulations showed a significant reduction from control in the τ 2 values. The longer relaxation time on the addition of TWEEN-80 to oleogels indicates the lesser likelihood of oleogels undergoing network architecture breakage [ 45 ]. In other words, the gelator network formed by the TWEEN-80 oleogels can maintain their structural integrity for an extended time under stressful conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, too, it was found that there was an increase in the force values with the corresponding increase in the concentration of palmitic acid. Alteration in the mechanical properties of the oleogels with the alteration in the composition is a well‐documented phenomenon . The percentage of stress relaxation (%SR) was calculated as per the equation is given in Equation .…”
Section: Resultsmentioning
confidence: 99%